Electrically and Thermally Tunable Smooth Silicon Metasurfaces for Broadband Terahertz Antireflection. Issue 23 (9th October 2018) - Ding, Lu; Luo, Xianshu; Cheng, Liang; Thway, Maung; Song, Junfeng; Chua, Soo Jin; Chia, Elbert E. M.; Teng, Jinghua
Abstract: Researches in metamaterials and metasurfaces have significant impact on development of terahertz optics and progression of terahertz science and technologies. Further advancement of terahertz systems demands efficient and versatile tunable and reconfigurable metadevices for manipulating various properties of terahertz radiation. Here an electrically and thermally tunable silicon metasurface for broadband terahertz antireflection application is demonstrated. The silicon metasurface is composed by interdigitated p–n junctions fabricated using a completely complementary metal‐oxide‐semiconductor (CMOS) compatible process in a silicon photonics foundry. It is atomically smooth without any physically etched pattern nor metal antennas. By supplying bias voltage to the p–n junctions, the complex reflection coefficient of the silicon metasurface is continuously tuned between negative and positive values. Complete antireflection condition can be precisely achieved, represented by the vanishing of the echo pulse in terahertz time‐domain spectroscopy (THz‐TDS). The transmission amplitude is bias‐polarity dependent, while the phase is simultaneously manipulated. The active silicon metasurface has a unique property that it thermally tunes the reflection and electrically tunes transmission. The methodology suggests a new design concept using all‐silicon platform for making atomically smooth and electrically controlled metadevices in terahertz and other frequency ranges. Abstract : An atomically smooth active silicon metasurface comprising interdigitated p–n junctions for broadband terahertz antireflection is demonstrated by using a completely complementary metal‐oxide‐semiconductor (CMOS) compatible fabrication process. Applying the electric bias voltage to p–n junctions, the complex reflection coefficient is continuously tuned between negative and positive values due to thermo‐optical effect and the transmission amplitude has unique bias‐polarity dependence. Antireflection condition is precisely achieved.